Mite Infestation Induces a Moderate Oxidative Stress in Short-Term Soybean Exposure - Wesley Borges Wurlitzer; Julia Renata Schneider; Joaquim A. G. Silveira; Maria Goreti de Almeida Oliveira; Noeli Juarez Ferla (Plants)
Phytophagous mites are herbivores that feed on various economically important plants, such as soybean [Glycine max (L.) Merril]. Thus, our objective is to evaluate the oxidative stress stage of soybean plants infested by Tetranychus ludeni Zacher. Leaflets from three trifoliate leaves were pooled to form composite samples for each exposure time and evaluated at the following evaluation times: 0 h, 20 min, 6 h, 12 h, 24 h, and 48 h. In the initial phase of infestation (20 min), an oxidative burst was observed, represented by prominent hydrogen peroxide accumulation rather than superoxide radicals. This oxidative burst occurred in parallel to a strong increase in the antioxidant activities of catalase, ascorbate peroxidase, and glutathione S-transferase, but not in that of superoxide dismutase. These changes likely reflected an enhanced activation of signaling pathways involved in the oxidative stress response. After this initial phase, from 20 min to 6 h, a prominent decrease occurred in catalase, ascorbate peroxidase, and glutathione S-transferases activities, despite the hydrogen peroxide levels remaining significantly elevated, along with a marked but transient increase in the reduced glutathione content and proline. Interestingly, superoxide dismutase activity increased significantly after 6 h in parallel to lipid peroxidation, whereas the content of hydrogen peroxide remained elevated until 12 h of infestation. By the final evaluation, after 48 h of infestation, some redox indicators remained altered in relation to control plants, but in a state of moderate redox stress. Thus, in an unprecedented way, our data suggest that T. ludeni infestation triggered a moderate oxidative stress response in soybean plants. These findings highlight that proper monitoring and management can reduce economic losses without resorting to aggressive chemical interventions.